Development of a Continuous Flow Hydride Generation Laser-Induced Breakdown Spectroscopic System: Determination of Tin in Aqueous Environments - Ünal, Semira; Yalçın, Şerife; Yalçın, Şerife (Elsevier Ltd., 2010)
The design, construction and optimization studies of a continuous flow hydride generation laser-induced breakdown spectroscopic system, HG-LIBS, for the determination of tin in aqueous environments is presented. Optimization of the Laser Induced Breakdown Spectroscopy (LIBS) signal with respect to carrier gas flow rate, analyte, acid (HCl) and reductant (NaBH4) concentrations and flow rates was performed by using spectral emission intensity from the neutral Sn(I) line at 284.0 nm under atmospheric pressures. With flow rates of 5.0 mL/min for NaBH4 and 2.5 mL/min for HCl, optimum NaBH4 and HCl concentrations were determined as 2.0% (w/v) and 1.0% (v/v), respectively. The hydride generation efficiency of the system was tested for tin hydride, stannane (SnH4), by inductively coupled plasma mass spectrometer (ICP-MS). It was found that higher than 99% of the analyte was released into the gaseous phase. Upon optimization, the minimum detectable Sn concentration was found as 0.3 mg/L in water samples. That corresponds to more than two orders of increase in sensitivity compared to methods that employ common sample introduction techniques in liquids analysis by LIBS. Over 90% recoveries were obtained from spiking experiments with river, tap and drinking water samples. Results illustrate potential use of the continuous flow HG-LIBS system for monitoring of Sn concentrations in aqueous environments. © 2010 Elsevier Ltd. All rights reserved.
A Selection of Papers Presented at the 5th Euro-Mediterranean Symposium on Laser Induced Breakdown Spectroscopy (EMSLIBS 2009)
Keywords: Environmental monitoring; HG-LIBS; Tin in aqueous samples; Volatile hydride